Large-Scale Seismic Vulnerability and Risk of Masonry Churches in Seismic-Prone Areas: Two Territorial Case Studies - Fabbrocino, Francesco; Vaiano, Generoso; Formisano, Antonio; D'Amato, Michele (Frontiers in Built Environment, 2019)
In this paper, seismic vulnerability and risk assessment of two samples of churches, located in Teramo and Ischia island (Naples gulf), both affected by the most recent earthquakes that occurred in Italy, are presented. To this aim, we applied a simplified method particularly suitable for seismic evaluations at a territorial scale, providing a global resulting score to be compared among the cases analyzed. The data obtained allowed us to provide vulnerability maps and a seismic risk index for all the considered churches. In addition, the calculated indexes permit a preliminary health state evaluation of the inspected churches, for ranking the priorities and planning additional in-depth evaluations.